O consumo materno perinatal de herbicida à base de glifosato prejudica o neurodesenvolvimento comportamental da prole. - Oliveira, Maria Aparecida De Lima (2021)
The increasing use of pesticides has worried the population. Glyphosate-based herbicides (GBH) are the main pesticides sold in Brazil and worldwide. Studies try to clarify the impacts brought about by the consumption of these substances present, mainly in food. Among the consequences already described are câncer, oxidative stress, depression and anxiety. Therefore, it was believed to be pertinent to investigate whether an GBH would be able to induce behavior similar to autism, since the prevalence of the disease has grown alarmingly worldwide, as well as the use of pesticides. Thus, the aim of the present study was to evaluate the effects of perinatal consumption of GBH by Wistar rats and the neurobehavioral alterations in offspring that characterize typical symptoms of autism and, finally, to search for the molecular mechanisms responsible for the alterations suffered. For this, pregnant Wistar rats received GBH, Zapp QI 620, by gavage during pregnancy and lactation. Our results showed that the glyphosate had a reduction in weight gain of the dams during the 16th and 19th day of lactation. During the assessment of maternal behavior, these dams also showed an increase in exploration without offspring. Finally, when evaluated in the open field test, the dams from the glyphosate group showed an increase in the total distance walked. As for the offspring, glyphosate females had a reduction in weight gain on the 28th postnatal day when compared to males in the same group. Glyphosate males had a reduction in the number of VUS, while glyphosate females had an increase in the repetitive behavior observed by the increase in the number of head dips in the hole board test. Glyphosate females and males had reduced play behavior. In the object recognition test, male glyphosate increased the familiar object exploration time and reduced the object recognition index in the 2 and 24 hours test. Proteins linked to neurogenesis and synaptic connections such as brain-derived neurotrophic factor (BDNF), Doublecortin (DCX) and Synaptophysin were quantified using the Western Blotting technique, but no differences were found between groups in the expression of any of the analyzed proteins. Based on the results presented, it’s concluded that the consumption of HBG by Wistar rats during the perinatal period can cause neurobehavioral changes similar to autism in offspring.